Enhanced exciton and photon confinement in Ruddlesden-Popper perovskite microplatelets for highly stable low-threshold polarized lasing - Li, Mingjie (2020)
At the heart of electrically driven semiconductors lasers lies their gain medium that typically comprises epitaxially grown double heterostuctures or multiple quantum wells. The simultaneous spatial confinement of charge carriers and photons afforded by the smaller bandgaps and higher refractive index of the active layers as compared to the cladding layers in these structures is essential for the optical-gain enhancement favorable for device operation. Emulating these inorganic gain media, superb properties of highly stable low-threshold (as low as ≈8 µJ cm-2 ) linearly polarized lasing from solution-processed Ruddlesden-Popper (RP) perovskite microplatelets are realized. Detailed investigations using microarea transient spectroscopies together with finite-difference time-domain simulations validate that the mixed lower-dimensional RP perovskites (functioning as cladding layers) within the microplatelets provide both enhanced exciton and photon confinement for the higher-dimensional RP perovskites (functioning as the active gain media). Furthermore, structure-lasing-threshold relationship (i.e., correlating the content of lower-dimensional RP perovskites in a single microplatelet) vital for design and performance optimization is established. Dual-wavelength lasing from these quasi-2D RP perovskite microplatelets can also be achieved. These unique properties distinguish RP perovskite microplatelets as a new family of self-assembled multilayer planar waveguide gain media favorable for developing efficient lasers.